Strategic Direction of Public Policy in Scenario Planning for Sustainable Conservation of Lake Limboto - Djafar, Franky; Akibu, Rifka S. (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
Lake Limboto, classified among the 15 national priority lakes, is undergoing a critical condition and is predicted to transform into dry land by 2035 due to an annual decrease in area of 65.89 hectares. This situation demands strategic policies that have not been fully visible or effectively implemented, necessitating a more comprehensive approach and initiative. To address these challenges, scenario planning becomes crucial. The research method employed is qualitative, focusing on "Scenario Planning for the Sustainable Conservation of Lake Limboto in Gorontalo Regency. Data were gathered through interviews, observations, and documentation, analyzed using an interactive analysis model, assisted by SWOT analysis, and PEST-Plus analysis. Serious threats to the sustainability of Lake Limboto in Gorontalo Regency emanate from three main aspects: economic, climatic, and political. The economic aspect creates an imbalance in the utilization of lake resources, requiring strengthening through training and the development of related sectors. Climatic conditions, especially the rise in air temperature, pose a serious threat that necessitates scenario planning and in-depth risk analysis. The political aspect indicates a lack of attention to lake preservation, requiring political commitment, resource allocation, and community participation. Despite the use of the TAIDA Approach (Tracking, Analyzing, Imaging, Deciding, Acting) in scenario planning, there are still some weaknesses in its implementation. In the context of sustainable development, further attention is needed regarding environmental protection and the sustainable management of lake resource consumption.